Marine Alien Species at Pserimos Island (Greece): census with the help of citizen scientists. (3rd April 2017) - Zenetos, Argyro; Liami, Aphrodite; Xentidis, Nicholas J.; Corsini-Foka, Maria
Abstract : Observations of citizen scientists have become an indispensable source in the collection of biodiversity data worldwide. In Greece, the findings of these citizen scientists, in collaboration with the Hellenic Network on Aquatic Invasive Species (ELNAIS), have resulted in compiling diverse information on marine alien species. Since 2004, the Liamis Dive Centre has recorded visual data on 12 marine alien species around Pserimos Island (Dodekanisa, Greece), thus enabling us to sequence their progression and displacement amongst other vital information. The real number of biological invasions is likely to be higher than reported here because citizen scientists do not have the scientific skills required for species identification and also due to financial constraints. Nevertheless, the high number of observers to a certain extent compensates the lack of taxonomic expertise.